The application on module of Tazkiyyah Al-Nafs in the spiritual development among students in Universiti Malaysia Pahang - Mohd Suhardi, Mat Jusoh; Hadijah, Ahmad; Anita, Abdul Rani (Universiti Malaysia Pahang, 2020)
The study on the usability Exercise Module of Tazkiyah Al-Nafs (MLTN) is a preliminary study to assess the application of spiritual development among students in Universiti Malaysia Pahang. The objective of the study is to identify the level of acceptance of this module among the participants, analyze the effectiveness of this module application and to assess the impact on the application of Exercise Module of Tazkiyah Al-Nafs in the aspect of improvisation. This exploratory study gathers the spiritual program exercise reflection and face to face interview with 15 participants who had to participate in the exercise program consistently. Inductive analysis has been conducted to answer the study aims such as what, why, and how as aligned with the qualitative nature. The overall findings indicate this module is accepted among the participants with two-element of effectiveness which is the consistency of the practice on Tazkiyah al-Nafs and the involvement of the teacher as guides in the spiritual exercise. This study recommends the consistency of the implementation of spiritual exercise programs to assess the impact on the module for further improvisation. In a nutshell, this module is desirable for the application on the spiritual development of students because the Islamic practice can uplift the value of quality spiritual among participants.